Pelatihan Cerita Anak Berbasis Budaya Minangkabau untuk Literasi Bagi Guru Sekolah Dasar - Alwi, Nur Azmi; Kenedi, Ary Kiswanto; Azizah, Zahratul; Zulkarnain, Aissy Putri; Mardin, Asna; Irwandi, Irwandi; Ulya, Ridha Hasnul (Universitas Pahlawan Tuanku Tambusai, 2025)
This training program aimed to enhance the capacity of elementary school teachers in developing and implementing children’s stories based on Minangkabau culture as a literacy tool. The background of this initiative is the limited ability of teachers to integrate local cultural values into contextual and engaging learning materials. The methods included training, story writing workshops, the production of teaching media, and classroom mentoring. The results showed a significant improvement in teachers’ conceptual understanding and writing skills, as well as the creation of culturally relevant storybooks. Implementation in the classroom also increased student engagement in literacy activities. This activity highlights the importance of culture-based literacy as a strategic approach in primary education, while reinforcing students’ local identity and character development from an early age.